Complete genome sequence of Geobacillus thermoglucosidasius C56-YS93, a novel biomass degrader isolated from obsidian hot spring in Yellowstone National Park. Issue 1 (December 2015) - Brumm, Phillip; Land, Miriam; Mead, David
Abstract Geobacillus thermoglucosidasius C56-YS93 was one of several thermophilic organisms isolated from Obsidian Hot Spring, Yellowstone National Park, Montana, USA under permit from the National Park Service. Comparison of 16 S rRNA sequences confirmed the classification of the strain as aG. thermoglucosidasius species. The genome was sequenced, assembled, and annotated by the DOE Joint Genome Institute and deposited at the NCBI in December 2011 (CP002835). The genome ofG. thermoglucosidasius C56-YS93 consists of one circular chromosome of 3, 893, 306 bp and two circular plasmids of 80, 849 and 19, 638 bp and an average G + C content of 43.93 %.G. thermoglucosidasius C56-YS93 possesses a xylan degradation cluster not found in the otherG. thermoglucosidasius sequenced strains. This cluster appears to be related to the xylan degradation cluster found inG. stearothermophilus. G. thermoglucosidasius C56-YS93 possesses two plasmids not found in the other two strains. One plasmid contains a novel gene cluster coding for proteins involved in proline degradation and metabolism, the other contains a collection of mostly hypothetical proteins.